Development of a sensitive monoclonal antibody-based ELISA for the determination of a β-adrenergic agonist brombuterol in swine meat, liver and feed samples. Issue 38 (8th September 2016) - Zhao, Yingying; Jiang, Danni; Wu, Kang; Yang, Hong; Du, Haijing; Zhao, Kang; Li, Jianguo; Deng, Anping
Abstract : A sensitive enzyme-linked immunosorbent assay (ELISA) based on a newly prepared monoclonal antibody (mAb) for the determination of a β-adrenergic agonist brombuterol in swine meat, liver and feed samples was developed. Abstract : A sensitive enzyme-linked immunosorbent assay (ELISA) based on a newly prepared monoclonal antibody (mAb) for the determination of a β-adrenergic agonist brombuterol in swine meat, liver and feed samples was developed. The immunogen and coating antigen were synthesized by directly linking brombuterol to carrier proteins using the diazobenzidine method. Mice immunized with the brombuterol–bovine serum albumin (BSA) conjugate were utilized for mAb generation whereas brombuterol–ovalbumin (OVA) was used as the coating antigen for the development of ELISA. Two hybridoma clones (13D12 C1 and 4D11 C1 ) specifically secreting antibodies against brombuterol were successfully isolated. Under optimal conditions, the IC50 and LOD values of the ELISA for brombuterol based on the mAb secreted by the 13D12 C1 clone were found to be 0.56 ng mL −1 and 0.047 ng mL −1, respectively. The ELISA displayed no cross-reactivity with structurally related β-agonists (ractopamine, salbutamol, phenylethanolamine A, phenylephrine and isoproterenol) and five other veterinary drugs, but showed 52.8% cross-reactivity with clenbuterol. Swine meat, liver and feed samples were spiked with different content of brombuterol and detected by ELISA. The recovery rates and the coefficients of variation of the intra-assay and inter-assay were found to be in the range of 87.3–107.5% and 3.5–11.6% ( n = 3), and 85.7–116.0% and 4.1–12.7% ( n = 3), respectively. Spiked samples were analyzed by ELISA and HPLC simultaneously. A good correlation between the two methods was obtained. The results demonstrated that the proposed ELISA was a feasible quantitative/screening method for brombuterol analysis in swine meat, liver and feed samples with the properties of high sensitivity, high sample throughput and low cost.